‫الرقابة‬‫على‬ ‫تكاليف‬ ‫الجودة‬ ‫و‬ ‫دورها‬ في‬ تحسين ‫الأداء‬ المالي ‫للمؤسسة‬ ‫‪‬‬‫دراسة ‬‫حالة‬ ‫عينة‬ ‫من‬ ‫المؤسسات‬ في‬ ‫ولاية‬ ‫سوق‬ ‫أهراس‬ ‫‪ - أميرة ورتاني‬ (My University, 2018)
The success of the companies and their progress in our time depends on the delivery of high quality products and free of defects in order to meet the requirements of the customer, so the company must make a series of sacrifices and costs to achieve the desired level of quality, which is called the costs of quality, In order to achieve this, the institution must provide a good system of control over these costs because of the impact on improving financial performance, so this study aimed to identify the role of control over the cost of quality in improving the financial performance of enterprises during the period 2017-2018, In our study we have been exposed to an important type of cost, which is of great importance in raising performance, especially financial performance, which is the cost of the quality borne by the companyto prevent defects or to handle products of poor quality On the production systems and on many quality control programs and associated costs The main objective of the organization is to win and achieve customer satisfaction Therefore it works to improve quality by making a series of sacrifices to eliminate the poor quality, Customer satisfaction and increased profits in the organization and ultimately all these factors lead to improving the financial performance of the institution. In order to achieve the objectives of the study a case study was conducted The questionnaire was designed and distributed to a sample of a community consisting of three economic companies The preliminary results data were analyzed using (SPSS). The study concluded that there is a relatively strong positive relationship between the control of the cost of quality and the financial performance, which confirms the knowledge of the studied companies on the cost of quality and control and the impact on the improvement of financial performance. The study concluded with several recommendations, the most important of which is that the companies should monitor the cost of quality on an ongoing basis and try to reduce it, especially the costs of failure of both types (internal and external) because they have the most impact on the reputation of the company to the maximum extent possible, as well as the need to increase the studies in the field of quality and costs And how to control them, because of the lack of studies in this area because of their significant impact in improving the financial performance of the company.